Phase I Dose‐Escalation Study of Ramucirumab in Chinese Patients with Advanced Solid Tumors. (2nd May 2017) - Cao, Junning; Ji, Dongmei; Chen, Zhiyu; Shen, Weina; Wang, Jin; Li, Baoyue; Chi, Haidong; Long, Amanda; Gao, Ling; Li, Jin
Abstract : Lessons Learned : Ramucirumab was well tolerated in Chinese patients with advanced solid tumors, and adverse events were manageable in this study. Pharmacokinetics characteristics in Chinese patients were similar to those in other populations. Immunogenicity was not detected. No efficacy conclusion could be drawn, and further randomized studies are warranted. Background: This single‐arm, nonrandomized, open‐label, dose‐escalation, phase I study was designed to evaluate the safety, tolerability, and pharmacokinetics (PK) of ramucirumab in Chinese patients with advanced solid tumors that were resistant to standard therapy or no standard therapy was available. Methods: Dose escalation was a 3 + 3 design, with expansion in Cohorts 2 and 3 for PK. Ramucirumab was given intravenously at three different dosages: 6 mg/kg every 2 weeks, 10 mg/kg every 3 weeks, and 8 mg/kg every 2 weeks. Safety analyses included all patients. PK, immunogenicity, and antitumor activity were also assessed. Results: Among 28 patients treated, 2 experienced dose‐limiting toxicity, possibly related to ramucirumab. No maximum tolerated dose was determined. All patients experienced at least one treatment‐emergent adverse event. Grade ≥3 adverse event was reported for 53.6% ( n = 15) of patients. PK analyses indicated that ramucirumab had low clearance, small volume of distribution, and long half‐life in Chinese patients, as in other populations. Immunogenicity was not detected. No patient had complete/partial response, and 64.3% ( n = 18) had stable disease with a median duration of 5.55 months (95% confidence interval: 3.38−7.13 months). Conclusion: Ramucirumab appeared to be well tolerated in Chinese patients with advanced solid tumors. PK characteristics in Chinese patients were similar to those in other populations.